A Multidimensional Feasibility Study for Establishing a Vocational Training Center in South Lampung Regency - Novalia, Novalia; Mauliana, Yunita; Josiah, Trisnowati; Pradana, Kenny Candra (Universitas Sang Bumi Ruwa Jurai, 2025)
The open unemployment rate in South Lampung Regency remains high, particularly among high school graduates who lack job-ready skills. This study aims to assess the feasibility of establishing a vocational training center (Balai Latihan Kerja/BLK) using a multidimensional approach based on nine aspects outlined in the Regulation of the Minister of Manpower (Kemnaker) No. 8 of 2017. A qualitative descriptive method was applied, involving observation, questionnaires, and interviews with 100 respondents. The feasibility assessment covers employment, demographics, geography, law, socio-cultural aspects, economy, science and technology, management, and funding. The findings suggest that the proposed Vocational Training Center (BLK) is deemed feasible across all assessed dimensions. The majority of respondents expressed the need for training in Information and Communication Technology (ICT), supported by demographic factors and location readiness. The training has been shown to improve skills, facilitate employment absorption, and foster entrepreneurial interest. In conclusion, the establishment of a BLK in South Lampung has strong potential to improve workforce quality and reduce unemployment. Government commitment, industrial collaboration, and continuous development of facilities and training programs are essential. Future research is recommended to evaluate the post-establishment impact of the BLK on employment absorption and local economic development.